2022
DOI: 10.1155/2022/4169150
|View full text |Cite
|
Sign up to set email alerts
|

Identification of m6A-Related lncRNA to Predict the Prognosis of Patients with Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death worldwide. In the past decades, HCC treatment has achieved great progress; however, the overall prognosis remains poor. Therefore, it is the need of the hour to identify new prognostic biomarkers which can advance our understanding related to the underlying molecular mechanism of adverse prognosis and apply them to clinical work in prognosis prediction. In the present study, data of 576 HCC patients and 292 normal control cases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Several bioinformatic studies revealed that Snhg1 was a m6A related lncRNA potentially involved in prognosis of patients with renal clear cell carcinoma and HCC. 3,21 Moreover, a comprehensive pan-cancer analysis of the prognostic and immunological roles of lncRNAs indicated that Snhg1 expression was regulated by the m6A writer METTL3. However, the involvement of Snhg1 in m6Amediated expression of other genes has not been exactly characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several bioinformatic studies revealed that Snhg1 was a m6A related lncRNA potentially involved in prognosis of patients with renal clear cell carcinoma and HCC. 3,21 Moreover, a comprehensive pan-cancer analysis of the prognostic and immunological roles of lncRNAs indicated that Snhg1 expression was regulated by the m6A writer METTL3. However, the involvement of Snhg1 in m6Amediated expression of other genes has not been exactly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…m6A is a very extensive and important RNA modification in human and animal cells, which is refined controlled by three types of m6A related RNA binding proteins, including writers (m6A methyltransferases), erasers (m6A demethylase), and readers (m6A recognition proteins). Several bioinformatic studies revealed that Snhg1 was a m6A related lncRNA potentially involved in prognosis of patients with renal clear cell carcinoma and HCC 3,21 . Moreover, a comprehensive pan‐cancer analysis of the prognostic and immunological roles of lncRNAs indicated that Snhg1 expression was regulated by the m6A writer METTL3.…”
Section: Discussionmentioning
confidence: 99%
“…Bicalutamide, a first-generation non-steroidal androgen receptor (AR) antagonist, has become a key part of prostate cancer (PCa) treatment by acting directly on the AR 61 . In Hepatocellular carcinoma (HCC), low expression of SNHG1/SNHG3 was more sensitive to bicalutamide 62 . In a lncRNA prognostic risk model of gastric cancer patients, high-risk patients were more sensitive to chemotherapeutic agents such as bicalutamide compared to the low-risk group 63 .…”
Section: Discussionmentioning
confidence: 99%
“…GABPB1-AS1 is involved in controlling oxidative stress during erastin-induced ferroptosis in HCC cells [ 18 ]. Additionally, Yang et al have stated that SNHG1 and SNHG3 promote the proliferative, migratory, and invasive abilities of HCC cells [ 19 ]. However, there are few studies analyzing the functions of long intergenic non-protein coding RNA 659 (LINC00659) in malignant diseases [ 20 , 21 ], HCC included.…”
Section: Introductionmentioning
confidence: 99%